Fear appeals and stigmatization in HIV/AIDS communications. - Nguyen, Thi Thanh Huong. (2008)
Based of the Extended Parallel Process Model (EPPM), this research explores the effects of fear appeal messages and the negative portrayal of HIV-infected persons on the stigmatization and discrimination against people living with AIDS.